Experimental influence of twist angle and cryogenic gas on quality of drilled hole in carbon fiber reinforced plastic composites. (May 2020) - Tran, Quang-Phuoc; Tsai, Ming-Chang; Hsiao, Te-Ching; Huang, Shyh-Chour
The considerable body of literature on the effect of moisture on the mechanical properties of composites has shown that there is a disinclination to use coolant fluids within the composite industry. Tool geometry and cryogenic liquid cooling also have a significant impact on carbon fiber–reinforced plastic machining capabilities. In this paper, the two issues mentioned are improving the drilled hole quality and reducing the amount of CO2 released into the air to protect the environment. The experimental characteristics using a carbide drill with three levels of twist angle of flute and a gas mixture of CO2 –N2 were investigated. To verify hole quality, the diameter, the delamination, the uncut fiber area, and the surface roughness were analyzed. With the goal of reducing the amount of CO2 released into the atmosphere, a list of experiments was proceeded in the dry, the air, gas CO2, and a gas mixture of CO2 –N2 . The thrust force and the temperature were observed. Based on the experiment results, the high helix tool was more advantageous than the triple tool and low helix tool. The difference in the effect of CO2 and CO2 –N2 was not significant with the triple tool and the low helix tool; however, the performance of the CO2 –N2 gas mixture showed a positive effect on the high helix tool.